RESEARCH ON PHYSICAL AND MECHANICAL CHARACTERISTICS OF FRONT BLOCKBOARDS MADE FROM POST-CONSUMER WOOD - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2016)
The expediency of using post-consumer wood ( PCW) for material production is substantiated. It is proposed to process PCW into blockboards (BB). Proposed are new designs of PCW-made blockboards which are suitable for manufacturing furniture fronts. It was experimentally confirmed that the physical and mechanical properties of front PCW-made blockboards meet the requirements of standards. Obtained are patterns of influence of the width of the core strips of the blockboard and the thickness of the facing wood fiberboard (WFB) on dimensional stability, strength at static bending across the strips and strength in shearing along the glue line of front PCW-made blockboards in the dry state. Adequate regression models are obtained that can be used to describe a study object. Practical recommendations are offered for the production and use of front PCW-made blockboards for furniture production.